Association between elevated weekend mortality and the seven-day hospital services programme in England: A retrospective longitudinal study. Issue 11 (November 2019) - Underwood, Charlotte; Sutton, Matt; Meacock, Rachel
Highlights: Weekend effect in mortality persists despite widespread adoption of seven-day clinical standards. Further adoption of the policy is not predicted to eradicate the weekend effect. England's policy is not a beneficial way to respond to the weekend effect. Abstract: Background: Patients admitted to hospital at weekends experience higher mortality rates than those admitted during the week. The NHS in England has taken the lead internationally with attempts to tackle this issue. Four priority clinical standards for emergency care have been introduced with the aim of reducing the 'weekend effect'. We investigate whether implementation of this policy has been associated with changes in the weekend effect. Methods: Retrospective observational study of 120 hospital Trusts in England. We use data on Trusts' performance against the clinical standards in 2015 and 2017, and estimates of Trusts' weekend effects in risk-adjusted mortality in financial years 2015/16 and 2016/17. We examine whether adoption of the standards is associated with the weekend effect. Results: We detect little association between Trusts' mortality weekend effects in 2016/17 and their performance against the clinical standards in 2017. Changes in achievement of the standards between 2015 and 2017 were not associated with changes in the weekend effect between 2015/16 and 2016/17. Discussion: Large improvements in performance against all four standards have not translated into reductions in the weekend effect. We find no evidence that England's policy is a beneficial way for health systems to respond to this phenomenon. Given the failure of the policy to achieve its aim, the current mandate for full compliance by 2020 requires urgent review.